Fintech Lending: Threat or Opportunity for Sharia Bank In Indonesia? - Aini, Ihdi; Asmadia, Tezi; Agusti, Netta (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
Data on the percentage of financing distribution to sharia banks in Indonesia in the last 5 years has experienced quite slow growth compared to the percentage of loan distribution by fintech lending which has experienced very significant growth, reaching 2,390.4% from 2018 to February 2023. The literature shows that there are two opposing views regarding the influence of fintech lending on banking. On the one hand, fintech plays an important role in increasing financial inclusion, while on the other hand fintech also has a major impact on the financial services industry. The aim of this research is to examine the influence of fintech lending on financing at Islamic banks in Indonesia and to analyze the impact of fintech lending on Islamic banks in Indonesia. This study uses a quantitative approach. The type of data used is secondary data taken from the official website of the Financial Services Authority (OJK) in the form of statistical data on sharia banks and fintech lending. The number of samples used was 60 financial report data obtained from sample selection through purposive sampling. The data analysis technique uses descriptive statistical analysis with a linear regression analysis model. The results of this research show that 88.9% of fintech lending has an influence on sharia bank financing in Indonesia. In the sense that fintech lending companies exist as complements or complements to sharia banks in providing financial loans to the public, therefore fintech lending can be an opportunity for collaboration for the sharia banking industry in Indonesia. This collaboration can be carried out using several patterns or models, including cooperation through cross-selling schemes, channeling, references, shadow investors, outsourcing platforms and fintech consortiums.